2019
DOI: 10.2174/1874471011666180831101459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Radioprotective Effect of Curcumin on Rat’s Heart Tissues

Abstract: Curcumin could reduce radiation-induced heart injury markers in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…This finding made us consider the possibility of metformin to prevent radiation‐induced heart damages. This was similar to curcumin, that suppresses the up regulation of transcription factors such as NF‐kB and immune mediators like COX‐2 after radiation exposure, thus curcumin can ameliorate genotoxicity and enhancement late effects of ionizing radiation as well as carcinogenesis …”
Section: Discussionmentioning
confidence: 65%
“…This finding made us consider the possibility of metformin to prevent radiation‐induced heart damages. This was similar to curcumin, that suppresses the up regulation of transcription factors such as NF‐kB and immune mediators like COX‐2 after radiation exposure, thus curcumin can ameliorate genotoxicity and enhancement late effects of ionizing radiation as well as carcinogenesis …”
Section: Discussionmentioning
confidence: 65%
“…Before irradiation, rats were anesthetised via an intraperitoneal injection of ketamine 10% (80 mg/kg) and xylazine 2% (5 mg/kg). Afterwards, they were irradiated with a 10 Gy single dose to the abdominal and pelvis region using a cobalt-60 gamma ray source at a dose rate of 0.65 cGy per minute and a source to skin distance of 1 m. The choice of the curcumin dose was based on a previous study by Kolivand et al, 7 while that of radiation was according to Jourdan et al 8 All rats were sacrificed 1, 2, or 4 weeks after irradiation. Afterwards, their skin tissues were carefully removed and frozen at −80°C.…”
Section: Study Design and Irradiationmentioning
confidence: 99%
“…Their results 10 weeks after irradiation showed that curcumin attenuated the upregulation of IL-4 protein and its receptor, IL4Ra1, as well as prevented infiltration of lymphocytes and macrophages. It also attenuated the expression of dual oxidases (Duox1 and Duox2), enzymes responsible for the stabilization of extracellular matrix via oxidative cross-linking [74].…”
Section: Curcuminmentioning
confidence: 99%